Modeling of crack formation in materials under explosion loads - Aptukov, Valery Nagimovich; Iljushenko, Pavel Nikolaevich; Fonarev, Alexey Vladimirovich (Computational Continuum Mechanics, 2010)
Based on the explicit finite-difference scheme, earlier modernized for the case of irregular meshes and local automatic refinement, we simulate fracture processes in materials subjected to the action of detonation products. An algorithm for numerical modeling of tensile and shear cracks is developed. The approach presented in this paper is used to design an auxiliary program module for software package EXPLOSION. Examples illustrating how to apply the proposed package product for solving the problem of crack formation in rock mass under the action of detonation products are given.